Jelajah Ceria: Transformasi Strategi Bermain Sambil Belajar untuk Optimalisasi Tumbuh Kembang Anak Usia Dini - Mutmaina Djafar; Nunung Suryana Jamin (Lembaga Pengembangan Kinerja Dosen, 2026)
Early childhood represents a critical foundational phase for cognitive, motor, and socio-emotional maturation. Traditional instructional models frequently encounter limitations in addressing individual developmental variances, thereby necessitating innovative, learner-centered pedagogical interventions. This community service initiative implemented the